Oncogenic KRAS supports pancreatic cancer through regulation of nucleotide synthesis. Issue 1 (December 2018) - Santana-Codina, Naiara; Roeth, Anjali; Zhang, Yi; Yang, Annan; Mashadova, Oksana; Asara, John; Wang, Xiaoxu; Bronson, Roderick; Lyssiotis, Costas; Ying, Haoqiang; Kimmelman, Alec
Abstract Oncogenic KRAS is the key driver of pancreatic ductal adenocarcinoma (PDAC). We previously described a role for KRAS in PDAC tumor maintenance through rewiring of cellular metabolism to support proliferation. Understanding the details of this metabolic reprogramming in human PDAC may provide novel therapeutic opportunities. Here we show that the dependence on oncogenic KRAS correlates with specific metabolic profiles that involve maintenance of nucleotide pools as key mediators of KRAS-dependence. KRAS promotes these effects by activating a MAPK-dependent signaling pathway leading to MYC upregulation and transcription of the non-oxidative pentose phosphate pathway (PPP) gene RPIA, which results in nucleotide biosynthesis. The use of MEK inhibitors recapitulates the KRAS-dependence pattern and the expected metabolic changes. Antagonizing the PPP or pyrimidine biosynthesis inhibits the growth of KRAS-resistant cells. Together, these data reveal differential metabolic rewiring between KRAS-resistant and sensitive cells, and demonstrate that targeting nucleotide metabolism can overcome resistance to KRAS/MEK inhibition. Pancreatic ductal adenocarcinoma (PDAC) cells display varying degrees of reliance on oncogenic KRAS. Here the authors show that KRAS-resistant PDAC cells maintain nucleotides synthesis through a KRAS-independent upregulation of the non-oxidative pentose phosphate pathway gene RPIA and that targeting nucleotide metabolism restore sensitivity to KRAS pathway inhibition.